Surviving the Tide: Assessing Guiana dolphin persistence amidst growing threats in a protected estuary in South-eastern Brazil - Guion de Almeida, Inaê; Reis Percequillo, Alexandre; Manoel Rollo, Mario [UNESP] (Elsevier, 2024)
This study investigated the population viability of Sotalia guianensis in the Cananéia Estuarine-Lagoon Complex, considering current and potential future scenarios. Simulations, using VORTEX software v. 10.5.5.0, spanned 100 years and were iterated 1000 times. Scenarios encompassed adjustments to demographic and environmental factors, evaluating population trajectories (baseline; increase fisheries; increase tourism; and increase harbour activity scenarios). Findings revealed a potential stochastic growth rate and population stabilization in baseline and increase tourism scenarios when major threats were absent. Conversely, increase fishing and harbour activity scenarios exhibited population decline, leading to eventual extinction within 100 years. Projected growth rates for all Scenarios were 0.0298 (SD=0.0424), −0.2650 (SD=0.2825), 0.0294 (SD=0.0654), and −0.0334 (SD=0.1145) respectively, with extinction probabilities of 0.0 for baseline and increase tourism scenarios, 1.0 for increase fishing scenario with mean estimated extinction time at 14 years, and 0.4430 for increase harbour activity scenario with mean estimated extinction time at 80.1 years. Sensitivity testing identified the percentage of adult females breeding and female mortality as the parameters most significantly impacting population trends. The simulations provided important insights into the primary factors impacting the viability of Sotalia guianensis and lay the groundwork for future population assessments and conservation plans.
Keywords: Conservation; Extinction; Population viability analysis; Sotalia guianensis; VORTEX